Mesoamerican Codices Calendrical knowledge and ceremonial practice in Indigenous religion and history - Frassani, Alessia (BAR International, 2022)
Religious manuscripts from ancient and early colonial Mexico offer a direct pathway into indigenous worldviews through the uniquely Mesoamerican medium of pictography. During the thousands of years preceding Spanish invasion, a complex calendrical system developed in the region, forming the basic organizing principle of this pictorial language. This book offers new interpretations and insights on both calendrics and the related iconography of Mesoamerican religious manuscripts, based on the author's field work in the Sierra Mazateca in northern Oaxaca. Detailed calendrical analysis is included, along with audio recordings of chants, prayers, and ceremonies available as an online download. The author's novel approach questions accepted notions of divination, chronology, and the dichotomy between ritual and historical time.